1987
DOI: 10.1093/genetics/115.1.121
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Dysgenesis in Drosophila melanogaster: Evidence from Sterility and Southern Hybridization Tests that P Cytotype Is Not Maintained in the Absence of Chromosomal P Factors

Abstract: A two-generation crossing program was used to replace the entire chromosome complement of P strains by M strain chromosomes, the maternal contribution being from the P strain. The cytotype of chromosomally substituted females was indistinguishable from M strain cytotype, judged by the sterility of offspring from the cross of such females to P strain males. In addition, following replacement of the chromosomes, the level of DNA homologous to the P factor was sufficiently low to be explicable by low levels of P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(3 citation statements)
references
References 10 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…In particular, specific P or hobo derivatives, such as KP which are involved in P regulation (Black et al 1987) or Th, that may be implicated in hobo regulation (Periquet et al 1989) cannot account for the differences in the rates of mobilization of the two elements. Both P cytotype (Sved, 1987) and hobo repressor (our unpublished data) need the presence of P and hobo elements to be developed or maintained. Thus, the differences must be due to other strainspecific factors such as host-encoded proteins involved in the P and hobo transposition processes either by enhancing or reducing the production of the P or hobo transposases, or through inactivation of P or hobo transposases, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…In particular, specific P or hobo derivatives, such as KP which are involved in P regulation (Black et al 1987) or Th, that may be implicated in hobo regulation (Periquet et al 1989) cannot account for the differences in the rates of mobilization of the two elements. Both P cytotype (Sved, 1987) and hobo repressor (our unpublished data) need the presence of P and hobo elements to be developed or maintained. Thus, the differences must be due to other strainspecific factors such as host-encoded proteins involved in the P and hobo transposition processes either by enhancing or reducing the production of the P or hobo transposases, or through inactivation of P or hobo transposases, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…However, Engels (1979) found that although P activity was repressed in the germline of most nondysgenic females from an interstrain cross, about 40% were themselves M cytotype. Sved (1987) has shown that there is no maternal inheritance of P cytotype (in contrast to the strong maternal inheritance of M cytotype); P cytotype depends on the presence of P elements in the genome. Therefore the cytotype of F 2 individuals from a nondysgenic cross will depend on their chromosomal complement of autonomous and nonautonomous P elements.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies of the nature and inheritance of P cytotype (ENGELS 1979a, b, 198 1;KIDWELL 1985;SVED 1987) indicate that it is determined by a limited form of maternal transmission that is ultimately dependent on the genomic P elements. The molecular basis for P cytotype remains unclear.…”
mentioning
confidence: 99%